ANALISIS DINAMIKA KELOMPOKTANI SAGU DI DESA LUKUN KECAMATAN TEBING TINGGI TIMUR KABUPATEN KEPULAUAN MERANTI - Febri Adi Sinaga; Rosnita ' '; Eri ' Sayamar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this study is : The level dynamics of sago farmers' groups in the village Lukun districts Tebing Tinggi Timur district Meranti. This study uses survey. This research was conducted in the village Lukun districts Tebing Tinggi Timur district Meranti starting from April to July 2016. Making a total of 55 people were taken by sago farmers with Purpossive Sampling. Analysis of the data used are Skala Likert Analysis. These results indicate that : The level of farmer group dynamics sago in the village Lukun districts Tebing Tinggi Timur in the category “medium” with a score average 3,06. Keywords : Sago, Farmers Group Dynamics